ANTESEDENT ENVIRONMENTAL MANAGEMENT ACCOUNTING : A LITERATURE REVIEW - Fithri Suciati; Nurmala Anhar; Niken Safitri; Tuti Setiatin (Jurnal Proaksi, 2023)
Environmental Management Accounting (EMA) is a scientific development work on environmental accounting, which focuses on mitigating environmental costs and impacts resulting from corporate activities. The purpose of this study is to find out the latest EMA research developments, namely the last 5 years 2018 - 2022. This type of research is literature research on EMA using the Publish or Perish application, the National Library of Indonesia and ProQuest, resulting in publishers such as Taylor and Proques Francis Online, Wiley Online Library, Emerald, Elsevier, JIEMAR, an online magazine for accountants, the keyword is "Environmental Management Accounting". Most of the objects studied are manufacturing companies. Where the research results in many studies give positive results on the variables studied.